Etnografi Komunikasi Basapa Di Ulakan Tapakis Kabupaten Padang Pariaman - Ediyanti, Rahmi; Mulyodiharjo, Sumartono; Zumiarti, Zumiarti (LPPM Universitas Ekasakti, 2021)
The tradition of basapa to the Tomb of Tuanku Syekh Burhanuddin is known as the name bersafar which in the pronunciation of the Minangkabau tongue becomes basapa, where this tradition is a historical tour of Islam found in West Sumatra. The communicative situation is using the nonverbal language used during the basapa tradition procession in the form of alms or infaq, pilgrimage, praying, praying, eating food & drinks placed on the tomb, dhikr, tadarusan, sholawatan, teachings of the syattariyah tarekat, well water, kimo water, watering stones ampa, and took the sand of the tomb. Basapa tradition communicative event is an annual tradition that is held on the 10th of the safar month. Where at that time the pilgrims and the people involved would follow a series of processions in the basapa tradition in the form of gratitude to thank Sheikh Burhanuddin for what he had fought for. They believe there is another goal of local beliefs, namely by following the basapa tradition we get a more sustenance, health and avoid catastrophe and so on. The communicative action that occurs is that people who follow the basapa tradition have a code or signal that is mutually agreed upon, this code has various forms and meanings. Communication patterns that exist in the basapa procession are primary communication patterns, because the processions in the basapa tradition use many verbal and nonverbal symbols